Sustainable housing development in China: does financial institutions overcome the risks and challenges to sustainable housing? - Ma, Shaodong (Technological and Economic Development of Economy, 2024)
Housing industry is one of the major threats to global environment and resource depletion. Particularly in China, it is regarded as a major challenge due to massive population growth. The most common barriers involve; economic barriers and environmental barriers. Therefore, to promote sustainable housing development, the management of these barriers is most crucial. This study is an attempt to overcome these barriers with the help of financial institutions in the context of China. The sample of the study are construction sector employees which are selected through simple random sampling method. Partial Least Square (PLS) is employed as statistical tool to analyze the primary data. Results revealed the positive role of financial institutions to overcome the challenges related to the economic barriers and environmental barriers. Financing from banks for the sustainable housing schemes can reduce the economic barriers and help to fulfil the sustainable housing criteria. Similarly, the environment requirements can also be achieved through environmental policy developed by the banks in China. This study recommended the Chinese government to promote sustainable hosing development through the promotion of bank financing and implementation of banks environmental policies.Please view correction statement: Corrigendum: Sustainable housing development in China: does financial institutions overcome the risks and challenges to sustainable housing?First published online 14 March 2024